Analyzing the Impact of Publicity and e-WOM on Indonesian Tourists’ Visit Intention to Seoul through Destination Awareness and Preference: A Structural Equation Modeling Approach - Herstanti, Ghassani; Suhud, Usep; Handaru, Agung Wahyu (Journal of Applied Data Sciences, 2024)
This research explores the role of digital publicity and electronic word of mouth (E-WOM) in shaping Indonesian tourists' intentions to visit Seoul. By integrating destination awareness and preference as mediating variables, the study provides a holistic view of how publicity and EWOM interact to influence visit intentions. Digital publicity, including news coverage and promotional content on social media, raises initial awareness of Seoul by highlighting its attractions, culture, and experiences. E-WOM, expressed through online reviews, travel blogs, and social media shares, further enhances the perception of Seoul by providing authentic, peer-driven narratives. These user-generated insights are particularly impactful, as they foster trust and add an emotional dimension to tourists’ perception of the destination. Using a structural equation modeling approach, the study analyzes survey responses from Indonesian tourists to validate six core hypotheses, examining the direct and indirect effects of publicity and E-WOM on destination awareness, preference, and visit intention. Results indicate that both digital publicity and E-WOM significantly contribute to tourists' awareness and preference for Seoul, with preference being a particularly strong predictor of visit intention. The findings underscore the importance of aligning digital publicity efforts with targeted E-WOM strategies, enabling tourism marketers to build both cognitive awareness and emotional appeal, which ultimately drive visit intention. These insights are valuable for tourism stakeholders aiming to enhance destination marketing strategies, as they suggest that a combined approach—leveraging both structured publicity and organic E-WOM—can effectively increase a destination’s appeal. By focusing on creating authentic, accessible content and fostering positive online word of mouth, tourism authorities can better attract tourists and establish Seoul as a top choice for Indonesian travelers.